1999
DOI: 10.1016/s1097-2765(00)80460-8
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular V(D)J Recombination Is Prohibited Specifically at the Joining Step

Abstract: V(D)J recombination, normally an intramolecular process, assembles immunoglobulin and T cell receptor genes from V, D, and J coding segments. Oncogenic chromosome translocations can result from aberrant rearrangements, such as occur in intermolecular V(D)J recombination. How this is normally prevented remains unclear; DNA cleavage, joining, or both could be impaired when the recombination signal sequences (RSS) are located in trans, on separate DNA molecules. Here, we show that both trans cleavage and joining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
2
18
2
Order By: Relevance
“…Finally, it was reported that 12-and 23-RSSs on separate transiently transfected plasmids could mediate relatively efficient synapsis, coupled cleavage, and signal joint formation. This study also reported a specific and dramatic defect in coding joint formation if the two RSSs were in trans, which led to the proposal that mechanisms exist that selectively disfavor or inhibit coding joint formation in trans (26).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Finally, it was reported that 12-and 23-RSSs on separate transiently transfected plasmids could mediate relatively efficient synapsis, coupled cleavage, and signal joint formation. This study also reported a specific and dramatic defect in coding joint formation if the two RSSs were in trans, which led to the proposal that mechanisms exist that selectively disfavor or inhibit coding joint formation in trans (26).…”
mentioning
confidence: 73%
“…1) could be used to amplify joints for both the cis and trans configurations. This strategy is essentially identical to that employed in a recent analysis of the same issue (26). We also explored the effect of substrate topology by transfecting supercoiled, relaxed circular, and linearized forms of the substrates.…”
Section: Cis Versus Trans and The Effect Of Substrate Topological Stamentioning
confidence: 99%
“…prohibited at the joining step (26). On the other hand, by increasing the local concentrations of two separate recombination substrates, Tevelev and Schatz have observed a higher level of intermolecular joining products (50).…”
Section: Vol 20 2000 Formation Of Ij and Hj Induced By V(d)j Recombmentioning
confidence: 99%
“…In contrast, their irradiated nontransgenic littermates developed thymic lymphoma, as evidenced by invasive thymic masses that compromised respiration. transfected with two different recombination substrate plasmids, and this bias is enforced at the joining, rather than the cleavage, step of V(D)J recombination (51). However, in thymocytes from irradiated SCID mice, the ratio of cis-to-trans rearrangements is approximately 5:1 (80), suggesting that the absence of functional DNA-PK greatly promotes interlocus misjoining events.…”
Section: Discussionmentioning
confidence: 99%